2018
DOI: 10.1007/s00586-018-5707-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting medical complications in spine surgery: evaluation of a novel online risk calculator

Abstract: Purpose The preoperative prediction of medical complications is essential to optimize perioperative management. SpineSage™ is a free of charge online calculator to predict medical complications in spine surgery. The current study utilizes it in patients undergoing spine surgery to assess whether the predicted risks would correlate with the actual complication rate in clinical practice. Methods A total of 273 consecutive patients who underwent spinal surgery were assessed. The risk of medical complications was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…This calculator was further assessed by Kasparek et al on 273 patients and found similar AUC values of 0.85 for medical complications and 0.71 for major medical complications. The authors concluded that the calculator was accurate at determining complications following various spine procedures [14,15]. The benefits of this calculator are that it includes several surgery-specific variables and patient comorbidities.…”
Section: Spinesagementioning
confidence: 99%
See 1 more Smart Citation
“…This calculator was further assessed by Kasparek et al on 273 patients and found similar AUC values of 0.85 for medical complications and 0.71 for major medical complications. The authors concluded that the calculator was accurate at determining complications following various spine procedures [14,15]. The benefits of this calculator are that it includes several surgery-specific variables and patient comorbidities.…”
Section: Spinesagementioning
confidence: 99%
“…From a quality improvement perspective, risk estimation may help reduce adverse events and The Centers for Medicare and Medicaid Services (CMS) may soon incentivize surgeons to incorporate risk assessment tools into the informed consent process for elective surgery [4]. Growing interest and emphasis on the importance of risk prediction in the orthopedic community have led to the development of several automated risk calculators [5][6][7][8][9][10][11][12][13][14][15][16][17]. Automated risk calculators allow the user to input specific patient characteristics into a calculator for a specific procedure to produce an automated risk prediction of adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Kasparek and colleagues demonstrated the clinical applicability and effectiveness of an online spinal surgery complication risk calculator within 30 days of surgery for a prospective analysis of 273 patients. 35 They demonstrated a prediction of 14.7% versus the reported 16.1% for medical complications and 3.8% for major medical complications versus the reported 3.3% in the trial. AUC values were 0.71 and 0.85 for medical and major medical complications, respectively.…”
Section: Synthesis and Suggestionsmentioning
confidence: 87%
“…AUC values were 0.71 and 0.85 for medical and major medical complications, respectively. 35 Interestingly, those deformity predictive models that included radiographic features such as pelvic tilt or instrumented levels reported higher AUC values than those that strictly referenced patient demographic and medical comorbidities. Belykh and colleagues also relied heavily on radiographic features to yield a highly accurate predictive model with 90% accuracy using disk-height index, segmental range of motion, and Pfirrmann grade, for example.…”
Section: Synthesis and Suggestionsmentioning
confidence: 98%
“…Prone positioning during the surgery is associated with physiological changes and the surgery itself is associated with significant intraoperative blood loss and postoperative complications. [17][18][19] Surprisingly, little is known about the impact of IFM in this specific context. Therefore, we designed a before-after comparison study to investigate the impact of IFM implementation on the postoperative outcome of patients undergoing major spine surgery.…”
Section: Introductionmentioning
confidence: 99%